Exploring EFL Teachers’ Perception and Implementation of Project-Based Learning in the Context of the Merdeka Curriculum - Muhammad Irham; Murni Mahmud; Sultan Baa (International Journal of Language, Education, and Literature, 2025)
This study aims to describe the implementation of Project-Based Learning (PjBL) method in teaching English as a foreign language at SMA Negeri 9 Wajo. Using a descriptive qualitative approach, data were obtained through observation and semi-structured interviews with English teachers who implemented PjBL. The results showed that the implementation of PjBL includes six main stages according to Delisle's model, namely: connecting the problem, developing the structure, visiting and reviewing the problem, producing the product, and conducting evaluation. Despite challenges such as limited time and facilities, teachers managed to actively engage students through contextualized and collaborative projects. This study concludes that PjBL is a relevant and effective approach in improving students' English language engagement and skills in the EFL classroom.